Reality Radio, Second Edition : Telling True Stories in Sound - Dilworth, Alexa; Biewen, John (Book collections on Project MUSE., 2017)
"This new revised and expanded edition of Reality Radio celebrates today's best audio documentary work by bringing together some of the most influential and innovative practitioners from the United States, Canada, the United Kingdom, and Australia. With a new foreword and five new essays, this book takes stock of the transformations in radio documentary since the publication of the first edition: the ascendance of the podcast; greater cultural, racial, and topical variety; and the changing economics of radio itself"--